Effect of soaking and germination conditions on γ-aminobutyric acid and gene expression in germinated brown rice. Issue 2 (2nd April 2020) - Hussain, Syed Zameer; Jabeen, Rifat; Naseer, Bazila; Shikari, Asif Bashir
ABSTRACT: Four pigmented land races (Madew Zag-1, Madew Zag-2, Tangdhar Zag and Karnah Zag) and one high yielding variety (cv. Jhelum) were tested for production of γ-aminobutyric acid (GABA) rich brown rice through germination. Central composite rotatable design was used to determine the effect of germination conditions, i.e., soaking time (h), germination time (h), germination temperature (°C), and relative humidity (%) on GABA content. Regression model developed was highly significant ( P < .0001) with high coefficient of determination (R 2  = 0.98). The optimized conditions obtained were soaking time: 5.76 h; germination time: 40 h, and germination temperature: 35°C. The genetic variation among genotypes was also studied with respect to three glutamate decarboxylase cDNAs; OsGAD1, OsGAD2, and OsGAD3 . The maximum GABA synthesis during germination was recorded in Jhelum (48.18 mg/100 g) followed by Tangdhar Zag (44.40 mg/100 g). Gene expression of OsGAD3 was also upregulated maximum in Jhelum followed by Tangdhar Zag with a fold change of 22.368 and 19.472, respectively.